b=zc+m

Simple and best practice solution for b=zc+m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b=zc+m equation:


Simplifying
b = zc + m

Solving
b = cz + m

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Simplifying
b = cz + m

See similar equations:

| 77r^2+53r-40=0 | | 4(x+5)=3(x-2)-2x+2 | | 42*84*3.14=x | | 3x^3-x^2-10x=-x^2+2 | | Y+9.4=10 | | 10x*4=80 | | 3x-15=120 | | 11-11x=-14-10x | | -a+8.5=14.2 | | -3(5+5m)=75 | | 1x+8=5 | | -6(10+2x)=-192 | | 3s^2+7s^2-18s-42=0 | | 3x-6=x-3 | | k-9=11 | | 0.6(-6.53-2x)=-0.4x | | 8x-9=3-2x | | (x-9)(3x-1)=-52x-39 | | 2(x-1)-6= | | 7sin^2(x)-3=0 | | 1-(3x+4)2=(4x-1)2-(5x+2)2 | | x-7=7x+5 | | -2.0p=5(10-0.5p) | | 6-4x-7x^3=0 | | (t+2)(t-3)=6 | | 5(3z-1)-3(z+5)=9(z+1) | | 6v-7=-9+7v | | 8w^2-18+9=0 | | 264=xy+(7(y+1))+(2(y+2)) | | abs(x-5)=abs(5x+4)-1 | | abs(x-5)=abd(5x+4)-1 | | x-3+x+x+3=38 |

Equations solver categories